Evaluasi Kuantitatif serta Analisis Kerugian Mayor dan Minor pada Sistem Perpipaan NaOH 29–31% di Chlor Alkali Plant PT X, Porsea - Samuel Gideon; Yudika Chesy Betesda (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Accurate evaluation of head losses is essential in industrial systems transporting viscous chemical fluids, such as sodium hydroxide (NaOH), to ensure hydraulic efficiency and operational reliability, particularly in chlor alkali plants. This study analyses major and minor flow losses in the NaOH piping system at PT X Chlor Alkali Plant, Porsea, and evaluates the pipe design's hydraulic feasibility. After defining system parameters—including fluid properties, pipe geometry, and the number and type of fittings—technical calculations were conducted to assess flow profiles and pressure losses along two main pipe routes. A quantitative analysis using the Moody diagram and operational data reveals that minor losses dominate, contributing over 75% of total head loss in both routes. The total head loss remains within the pump's rated capacity (18 m), though with a narrow margin. A pipe diameter of 0.114 m produces a flow velocity of 0.79 m/s, aligning with recommended industrial standards for corrosive fluids. The use of Sch.80 stainless steel proves effective in minimizing frictional losses, particularly under turbulent flow conditions. These findings highlight the critical role of fitting configurations and material selection in optimizing chemical process piping systems.